2001
DOI: 10.1161/hh1601.095598
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A 2 in Vascular Disease

Abstract: Abstract-Secretory phospholipase A 2 (PLA 2 ) can be proatherogenic both in the circulation and in the arterial wall. In blood plasma, PLA 2 can modify the circulating lipoproteins and so induce formation of small dense LDL particles, which are associated with increased risk for cardiovascular disease. In the arterial wall, PLA 2 can hydrolyze lipoproteins. The PLA 2 -modified lipoproteins bind tightly to extracellular proteoglycans, which may lead to their enhanced retention in the arterial wall. The modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 110 publications
7
118
0
5
Order By: Relevance
“…C57BL/6 and 129/Sv)) show marked resistance to bacterial infection (19,20), thus substantiating the in vitro observations that this enzyme efficiently hydrolyzes bacterial membranes (21). In addition, sPLA 2 -IIA Tg mice show increased lipoprotein hydrolysis and atherosclerosis (22)(23)(24), although sPLA 2 -V and sPLA 2 -X have also been implicated in these processes (25,26). Mouse strains intrinsically deficient in sPLA 2 -IIA because of a frameshift mutation in its gene are susceptible to intestinal tumorigenesis (45).…”
Section: -X Mostly Remains Inactive Under Physiological Conditions Ansupporting
confidence: 70%
See 1 more Smart Citation
“…C57BL/6 and 129/Sv)) show marked resistance to bacterial infection (19,20), thus substantiating the in vitro observations that this enzyme efficiently hydrolyzes bacterial membranes (21). In addition, sPLA 2 -IIA Tg mice show increased lipoprotein hydrolysis and atherosclerosis (22)(23)(24), although sPLA 2 -V and sPLA 2 -X have also been implicated in these processes (25,26). Mouse strains intrinsically deficient in sPLA 2 -IIA because of a frameshift mutation in its gene are susceptible to intestinal tumorigenesis (45).…”
Section: -X Mostly Remains Inactive Under Physiological Conditions Ansupporting
confidence: 70%
“…Because of the secreted moiety of sPLA 2 s, it is likely that their target substrates also exist in the extracellular milieu. In fact, several sPLA 2 s hydrolyze phospholipids in bacterial membranes (19 -21), plasma lipoproteins (22)(23)(24)(25)(26), lung surfactant (27)(28)(29)(30)(31)(32)(33)(34)(35), and so on with distinct poten-cies in vitro, suggesting that they play divergent roles in various biological events. However, the proposed roles of sPLA 2 enzymes have largely been inferred from their enzymatic and biochemical properties, the effects of their overexpression or exogenous addition in in vitro experimental settings, or the use of pharmacological inhibitors (whose specificity may not be strictly defined).…”
Section: -X Mostly Remains Inactive Under Physiological Conditions Anmentioning
confidence: 99%
“…De Vries et al (68) have shown that monocyte-derived macrophages can lower their environmental pH to as low as 5.5 in the presence of oxidized LDL, a pH condition optimal for most cathepsins including cathepsin F. Interestingly, the acidification of the pericellular environment of macrophages is frequently coupled with the secretion of several cathepsins (23). Furthermore, lipolytic modifications of lipoproteins in the arterial intima, by producing free fatty acids, may also participate in the generation of an acidic microenvironment (69), and finally, the negatively charged glycosaminoglycan chains of proteoglycans may decrease the pH locally by attracting positively charged hydrogen ions (46).…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid is the key substrate for the synthesis of potent lipid mediators of inflammation. Several mammalian secretory PLA 2 s (sPLA 2 s) have been characterized and classified into different families (11). At present, 12 distinct sPLA 2 s have been identified in mammals and classified into different groups, depending on their primary structures as characterized by the number and position of cysteine residues.…”
Section: Controlled Degradation Of Extracellular Matrix (Ecm)mentioning
confidence: 99%